2001
DOI: 10.1046/j.1467-789x.2001.00029.x
|View full text |Cite
|
Sign up to set email alerts
|

Obesity prevalence and trends in Latin‐American countries

Abstract: The prevalence of obesity in some lower-income and transitional countries is as high as, or even higher than, the prevalence reported in developed nations, and it seems to be increasing rapidly. In most countries, the prevalence of obesity is higher in women than in men, and higher in urban than in rural areas. Preobesity prevalence is very high in most Latin-American countries. Sixty per cent of the population in Venado Tuerto (Argentina) has a body mass index (BMI) of > or = 25 kg m-2, as do 35% of the popul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
129
2
24

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 195 publications
(165 citation statements)
references
References 25 publications
10
129
2
24
Order By: Relevance
“…Recent data from the US, Australia, Latin America and a number of European countries consistently demonstrate that the prevalence of overweight and obesity is increasing exponentially in all age groups, [1][2][3][4][5][6][7] and is now of pandemic proportions. 8 Obesity is multifactorial, involving genetic, 9,10 physiological, 11 social, cultural and environmental components.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data from the US, Australia, Latin America and a number of European countries consistently demonstrate that the prevalence of overweight and obesity is increasing exponentially in all age groups, [1][2][3][4][5][6][7] and is now of pandemic proportions. 8 Obesity is multifactorial, involving genetic, 9,10 physiological, 11 social, cultural and environmental components.…”
Section: Introductionmentioning
confidence: 99%
“…In Latin America, the prevalence of undernutrition-related problems is decreasing while the prevalence of overweight and obesity is increasing, even among native groups (Filozof et al, 2001;Peña and Bacallao, 2001;Kain et al, 2002). In Bolivia, the only available data concerning anthropometry of adolescents are the regular Development and Health Surveys (DHS).…”
Section: Introductionmentioning
confidence: 99%
“…Compared with other studies that identified childhood overweight and obesity using weight-for-height Z-score cut-off points, the prevalence of overweight and obesity in children from this population is low in relation to other developing and developed countries and similar to that observed in less developed countries in Latin America 4,[23][24][25] . One study conducted in Argentina reported an obesity prevalence in children aged 24-72 months of 7.03%, ranging from 2.3% to 17.0%.…”
Section: Discussionmentioning
confidence: 50%
“…One study carried out with South American Indian groups, that defined obesity as BMI .27 kg m -2 , showed an obesity prevalence in rural adult Aymaras living in north Chile (geographically closer to the studied population) of 33%. When the same cut-off was applied to the present adult population, the prevalence of obesity was 31.9% (data not shown) 4,5 .…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation